Internship in education organization and management: experiences of a discipline - Aquino, Kenia Adriana de [UNESP]; Lima, Ezer Wellington Gomes; Garske, Lindalva Maria Novaes [UNESP] (Sindicato Secretarias Estado Sao Paulo, 2023)
This study deals with the Supervised Curriculum Internship in Education Organization and Management, which aims to bring the undergraduate student in Pedagogy closer to the social and educational sense of the institutions of Early Childhood Education and Elementary Education. This curricular component seeks, therefore, to offer an understanding of the importance of the Pedagogical Political Project (PPP) as an instrument of administrative and pedagogical organization, as well as the legislation that underlies its construction. In order to contribute to the development of a systemic and strategic vision of educational management, considering the pedagogical, administrative, financial and social aspects involved in the management of a school, this study reports an experience with students in the 6th semester of graduation in Pedagogy at the Federal University of Rondonopolis (UFR), enrolled in the Supervised Curricular Internship in Education Organization and Management. The results obtained from this experience enriched the effective knowledge of skills related to leadership, namely: communication; decision making; Problem solving; team work; negotiation and organization, which are essential for effective performance in the field of educational management.
Keywords: Teacher Training; Supervised Internship; Theory and Practice; Pedagogy; Experience Report